Clinical characteristics and prognosis in patients with a first acute heart failure hospitalization according to admission hyponatremia. Issue 4 (4th July 2018) - Formiga, Francesc; Chivite, David; Brasé, Ariadna; Petit, Irene; Moreno-Gonzalez, Rafael; Arévalo-Lorido, Jose Carlos; Corbella, Xavier
ABSTRACT: Objective Admission hyponatremia is related to poor outcomes in patients with heart failure (HF). Few studies have examined the influence of hyponatremia in the prognosis of HF patients without previous admissions. Our aim is to determine whether baseline hyponatremia predicts worse outcomes in a cohort of real-world HF patients admitted because of a first episode of acute HF. Methods We reviewed the medical records of 985 patients >50 years of age admitted within a two-year period for a first episode of decompensation of HF. We divided the sample according to the presence of hyponatremia, defined as serum sodium <135 mEq/L. We compared one-year all-cause mortality rates between groups, using Cox regression analyses. Results The patients' mean serum sodium at admission was 138 ± 4; 150 (15.2%) patients had hyponatremia. Hyponatremic patients had lower hematocrit values compared with the rest. Global mortality rates were higher across all evaluations (one, three, and 12 months) in the hyponatremia group, although statistical significance was not reached. After one year of follow-up no differences in patients' baseline sodium values were found between those who died and survivors (137.9 vs.138.6; p  = 0.05). Natremia at admission considered as a continuous variable (HR 0.971; IC 95% 0.945–0.997) was associated with mortality; however, multivariate Cox regression analysis did not confirm this association. Conclusions Admission hyponatremia is not uncommon even in patients admitted for the first time because of acute HF. However, hyponatremia in this cohort of patients does not seem to influence significantly in short- to mid-term mortality.